Hubungan Faktor Riwayat LILA, Riwayat Kenaikan BB dan Riwayat Kadar Hb Ibu dengan Kejadian BBLR di Kota Bontang - Maulida Ega Purnama; Lia Kurniasari (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Low Birth Weight is still a public health problem and occurs in many countries include Indonesia. The causes of LBW have been conceptualized in many theories, and many studies have been conducted to prove it so that efforts to improve it can be made. The incidence of LBW is closely related to nutritional status. The nutritional status of pregnant women both before and after pregnancy can describe the availability of nutrients in the mother's body to support fetal growth.This research was carried out using a Case Control design, carried out on mothers who have babies with a history of low birth weight and also normal. The results of the study were processed by the Chi Square test by showing the OR obtained by several factors that influence the incidence of LBW in Bontang City, namely a history of LiLa less than 23 cm is at risk of 4.6 times, a history of HB levels of less than 11 mg/dl is 4.7 times at risk, and a history of Weight gain during pregnancy < 6 Kg times the risk of 5.5 times for giving birth with low birth weight babies. There is still a need for strong cooperation from various parties to continue efforts to reduce the incidence of LBW, especially for pregnant women who are expected to always be able to pay attention to their pregnancy even though it is not their first pregnancy